A study of organizational culture on organizational performance in it sector from Hyderabad - Patlolla, Ramya; Reddy Doodipala, Mallikarjuna (International Journal of Engineering and Technology, 2018)
The study reveals about organizational culture dimensions on organizational performance within organization. Most of the studies believed that the organizational culture is playing a significant role in sustaining the competitive advantage to exaggerate the organizational performance by dynamic organizations. Motivated by this fact, the authors suggest the organizational culture dimensions influence on only performance and its must be under consideration. Therefore, the objective of this study is to analyse the relationship between the dimensions of organizational culture and organizational performance among IT companies operating in a state capital region. Relationship between dimensions and their influence on performance was also tested using factor analysis. For this, various dimensions of organization culture were identified from the previous literature and accordingly the questionnaire was made. This kind of analysis may be useful to improve the organizational performance and its quality of service (QoS) guarantee.Â Â Â